2022
DOI: 10.1186/s41182-022-00491-8
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with prolonged hospitalization of patients with corona virus disease (COVID-19) in Uganda: a retrospective cohort study

Abstract: Introduction Identification of factors predicting prolonged hospitalization of patients with coronavirus disease (COVID-19) guides the planning, care and flow of patients in the COVID-19 Treatment Units (CTUs). We determined the length of hospital stay and factors associated with prolonged hospitalization among patients with COVID-19 at six CTUs in Uganda. Methods We conducted a retrospective cohort study of patients admitted with COVID-19 between … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 23 publications
1
6
0
Order By: Relevance
“…Apart from this study, SARS-CoV-2 and malaria co-infection population studies have been conducted on nine malaria-endemic countries with heterogeneous results depending on the study design and the population or subpopulation studied ( S1 Table in S1 Text ). Most studies have evaluated malaria co-infection prevalence among COVID-19 confirmed patients reporting a wide range of prevalence from 0.63% to 100% (1721,23,26). Among the few studies that have analysed a random population sample, the low co-infection prevalence that we found in Equatorial Guinea (0.4%) is in the range with what has been reported from Nigeria (0.32%) (16), India (0.73%) (27), Burkina Faso (1.9%) (15), Angola (1.9%) (25) and Gabon (2.2%) (24).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Apart from this study, SARS-CoV-2 and malaria co-infection population studies have been conducted on nine malaria-endemic countries with heterogeneous results depending on the study design and the population or subpopulation studied ( S1 Table in S1 Text ). Most studies have evaluated malaria co-infection prevalence among COVID-19 confirmed patients reporting a wide range of prevalence from 0.63% to 100% (1721,23,26). Among the few studies that have analysed a random population sample, the low co-infection prevalence that we found in Equatorial Guinea (0.4%) is in the range with what has been reported from Nigeria (0.32%) (16), India (0.73%) (27), Burkina Faso (1.9%) (15), Angola (1.9%) (25) and Gabon (2.2%) (24).…”
Section: Resultsmentioning
confidence: 99%
“…Some other studies have addressed the clinical consequences of malaria and COVID-19 co-infection but with contradictory results. Recent retrospective studies of COVID-19 patients have found that malaria co-infection is associated with prolonged hospitalisation (26) and had greater mortality risk compared with just SARS-CoV-2 infection (23). However, other studies report that patients with SARS-CoV-2 and malaria did not seem to have a worst disease outcome, but previous malaria exposure seems to be related to less frequency of severe COVID-19 (20).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations